Polarization-dependent optical absorption of MoS(2) for refractive index sensing - Tan, Yang (Sci Rep, 2014)
As a noncentrosymmetric crystal with spin-polarized band structure, MoS(2) nanomaterials have attracts increasing attention in many areas such as lithium ion batteries, flexible electronic devices, photoluminescence and valleytronics. The investigation of MoS(2) is mainly focused on the electronics and spintronics instead of optics, which restrict its applications as key elements of photonics. In this work, we demonstrate the first observation of the polarization-dependent optical absorption of the MoS(2) thin film, which is integrated onto an optical waveguide device. With this feature, a novel optical sensor combining MoS(2) thin-film and a microfluidic structure has been constituted to achieve the sensitive monitoring of refractive index. Our work indicates the MoS(2) thin film as a complementary material to graphene for the optical polarizer in the visible light range, and explores a new application direction of MoS(2) nanomaterials for the construction of photonic circuits.